Parametric Study of Ring Creep in Wind Turbine Bearings: A FEA-Based Study of Structure-Induced Ring Creep in Wind Turbine Main Shaft Bearings - Katti, Nikhil Prasad (My University, 2026)
Ring creep, the progressive circumferential migration of a bearing ring relative to its seat is a critical failure mode in large-scale wind turbine main shaft bearings, where aerodynamic bending moments produce non-uniform contact pressure distributions that classical interference fit calculations cannot reliably predict. This study presents an FEA-based case study developed at SKF AECC to quantify the influence of aerodynamic load components on structure-induced ring creep in a generic multi megawatt wind turbine arrangement. A multi-scale simulation framework couples system-level bearing load extraction in SKF SimPro with a non-linear, quasi-static transient finite element analysis in ANSYS, where contact load vectors are rotated in discrete angular increments across the inner ring raceway of a submodel comprising the main shaft and inner races of two large-size tapered roller bearings. A load component screening study identifies Tilt and Yaw moments as the dominant contributors to ring creep, motivating a systematic parametric study across the operational Tilt–Yaw loading space. The resulting response surfaces reveal a clear non-linear relationship between the applied bending moments and the ring creep behaviour, identifying critical load thresholds beyond which the interference fit transitions from stable micro-slip into irreversible macro-wandering. Integration of the simulation results with a recorded operational load history further shows that ring creep damage in this configuration is driven primarily by normal power production loading rather than by extreme or rare load events, underscoring the practical importance of housing stiffness and interference fit specification at the drivetrain design stage. All quantitative results are specific to the structural stiffness of the generic housing and shaft geometry used in this study and should not be interpreted as generally applicable thresholds.
Keywords: ring creep; wind turbine bearings; structure-induced creep; interference fit; finite element analysis; tapered roller bearings; multi-scale modelling; multi-scale modelling; parametric study; bending moments; fretting wear